Analisis Faktor-Faktor Yang Mempengaruhi Dividend Payout Ratio Pada Perusahaan Sektor Manufaktur Di BEI - Kusumastuti, Ratih, Drs. Sri Padmantyo, M.B.A (2017)
This study was conducted to investigate the influence of variable Return on Assets (ROA), Debt to Equity Ratio (DER), Cash Position (CP), and the Growth againts Dividend Payout Ratio (DPR) on manufacturing companies listed in Indonesia Stock Exchange (BEI) during the period 2013 to 2015. The sample consisted of 15 companies that obtained using purposive sampling. The analytical method used in this research is multiple linear regression. The results showed that simultaneous ROA, DER, CP, and Growth showed a significant result. Partially, there are 2 (two) variables that have positive and significant effect on DPR of variable ROA and CP. Variable DER showed a negative and significant as more and more obligations, the income would be used to pay such obligations and will automatically reduce the amount of dividends distributed. In the variable growth results also negative and significant. This is because the company is in need of funds for expansion and investment needs. So investors should consider the variable ROA and CP in reference to the decision to buy or sell shares in connection with their expectation dividends are distributed.